The Cambridge history of the English novel - Caserio, Robert L., 1944-; Hawes, Clement (Cambridge : Cambridge University Press, 2012)
'The Cambridge History of the English Novel chronicles an ever-changing and developing body of fiction across three centuries. An interwoven narrative of the novel's progress unfolds in more than fifty chapters, charting continuities and innovations of structure, tracing lines of influence in terms of themes and techniques, and showing how greater and lesser authors shape the genre. Pushing beyond the usual period-centered boundaries, the History's emphasis on form reveals the range and depth the novel has achieved in English. This book will be indispensable for research libraries and scholars, but is accessibly written for students. Authoritative, bold and clear, the History raises multiple useful questions for future visions of the invention and re-invention of the novel'--
'Some important English novels have been popular; some have not; but ours is not a history of bestsellers. To be sure, the novel is not an entirely autonomous literary form, developing in isolation from the influence of market forces or of politics, national or international. Far from it: no one could seriously make such an argument. And yet if the novel sees at all - if it offers unique insights - it does so above all through the ceaseless making, breaking, and remaking of literary forms. Every decision that a novelist makes is formally mediated, and thinking through those decisions provides access to the history of the novel as such. By attending to this history of formal innovations one begins to understand the range and depth of which the English novel has been capable. We hope, even though the Cambridge History concludes by affirming the enduring power of romance, that our way of turning the novel's progress into history is less quixotic than the quest of the Knight of the Woeful Countenance'--
Includes bibliographical references (p. 887-900) and index.
Keywords: English fiction -- History and criticism